Analysis the Effect Perception of Stigma and Discrimination with the Time of Disclosure of Personal Status of Plwha in Sumenep District - Dian Permatasari; Eva Nurhidayati; Dian Ika Puspitasari (Global Health Science Group, 2020)
Human Immunodeficiency Virus and Acquired Immuno Deficiency Syndrome or HIV and AIDS has become an epidemic that very seriously threatens the health of people the world. The problem of HIV and AIDS is a health challenge in almost all over the world, including in Indonesia. East Java is one of the provinces witt the highest number of HIV/AIDS sufferers most in Indonesia. As of September 2018, the number of people living with HIV/AIDS was 47,396 people. The data obtained in the field shows that the number of PLWHA in East Java reached 47,396 patients as of September 2018. Research survey of analytic design of the study Cross sectional with a total sample of 30 respondents. How to capture samples of the study is using Total Sampling. At the study's Most large perception of stigma and discrimination of patients PLHIV most large still less capable of 17 people (56.67%) and as many as 13 people (43.33%) PLHIV patients have the perception of stigma is less capable. Analysis of these data do show that, there is the influence of the perception of people with HIV to stigma and discrimination by the time of the disclosure of the status of self- respondents to the spouse who obtained the result p value <0.000 (p < α or 0.000 <0, 05).